Model Pembelajaran Kolaborasi Hypno-Quantum Teaching Pada Mata Pelajaran Biologi - Rini Marianne Ulim (Jurnal Ilmu Pendidikan Indonesia, 2019)
The empirical facts found in class VII students showed that most students were less interested in the material being taught, monotonous learning so students seemed bored because they were less empowered. Quality learning outcomes require learning innovations that are appropriate and meaningful but still cool and fun. One of the innovations is the Hypno-Quantum Teaching learning model. The method used in this study was quasi-experimental with a sample of 80 people divided into two classes (control class and experimental class). The results showed that there were no differences in student interest but there were differences between hypno-quantum teaching and the class using conventional learning models, as evidenced by the value of 0.454 taken from the t-test.